(untitled) (The Review of Diabetic Studies, 2025)
This study aims to investigate the role of continuing professional development programs at the Saudi Red Crescent Authority in enhancing job satisfaction and improving employee performance. The study adopted the descriptive analytical approach, and a questionnaire consisting of (10) statements was applied to a sample of (200) employees. The questionnaire addressed several aspects, including the effectiveness of the training, the extent to which its content aligned with practical needs, the level of administrative support for implementing what was learned, the impact of training on motivation and the quality of professional performance, and the adequacy of resources and evaluation mechanisms. The results showed a general positive trend toward the effectiveness of development programs, with items related to motivation and the need to update systems scoring highest, while resources and time allocated to training scored lowest, indicating operational constraints that limit optimal utilization. The internal consistency indicators of the study scale (Cronbach’s alpha coefficient ≈ 0.87) also showed a good level of validity and reliability. The study recommended the need to enhance institutional support in terms of time and resources, update training program implementation mechanisms, and adopt a systematic system for evaluation and follow-up. She also stressed the importance of directing training efforts according to actual practical needs, which contributes to transforming acquired knowledge into tangible professional behavior and enhancing the quality of services provided by the Authority.